2020
DOI: 10.3390/ijerph17176148
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a “Music Beeps” Program to Promote Physical Fitness in Adolescents

Abstract: This study aimed to develop a physical education fitness program for adolescents to counteract the declining physical activity levels caused by the COVID-19 pandemic, as well as to investigate the program’s effect. This mixed-methods study developed and implemented a five-component “Music Beeps” (MB) program to promote adolescents’ physical fitness. A total of 240 students from two high schools in South Korea—divided into experimental and control groups—participated in 32 sessions over 16 weeks. The changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This new approach also adopted in the present study led to consistent positive changes in the SPPF for about 21.2% in girls and 26.4% in boys. Similar effects have been presented qualitatively or in average effects by other researchers [ 49 , 50 ], although traditional Physical Education classes provide more facilities for improving physical fitness and social interaction [ 12 , 29 , 39 , 40 , 47 , 48 ]. In another way, the online classes were adequate for some children, mainly when students create autonomy to learn and practice Physical Education at home, maintaining and improving healthy habits [ 51 ].…”
Section: Discussionsupporting
confidence: 75%
“…This new approach also adopted in the present study led to consistent positive changes in the SPPF for about 21.2% in girls and 26.4% in boys. Similar effects have been presented qualitatively or in average effects by other researchers [ 49 , 50 ], although traditional Physical Education classes provide more facilities for improving physical fitness and social interaction [ 12 , 29 , 39 , 40 , 47 , 48 ]. In another way, the online classes were adequate for some children, mainly when students create autonomy to learn and practice Physical Education at home, maintaining and improving healthy habits [ 51 ].…”
Section: Discussionsupporting
confidence: 75%
“…Developing online intervention programs of physical activity might be also a relevant strategy whether further mitigation would be taken. Indeed, many studies showed that a remote physical education intervention maintained or even increased physical fitness levels in children and adolescents [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The PAPS is a mandatory evaluation program performed once a year on all elementary, middle, and high school students in South Korea. In PAPS, physical fitness consists of five components (i.e., power, muscle strength and endurance, flexibility, cardiovascular endurance) [ 14 ]. The current study measured the essential PAPS evaluation items: 50 m run for power, sit-up for muscular strength and endurance), sitting trunk flexion for flexibility, and shuttle run for cardiovascular endurance [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Jeong and colleagues (2020) applied the intervention combining physical fitness training and cognitive modification strategies for 16 weeks to 120 female adolescents. The results indicated that physical fitness (i.e., power, muscle strength and endurance, flexibility, and cardiovascular endurance), as well as psychological variables such as self-efficacy and perceived benefits, and motivation are significantly improved after the intervention [ 14 ].…”
Section: Introductionmentioning
confidence: 99%